Estilos de aprendizaje y compresión lectora en estudiantes de IV ciclo de Primaria de la Institución Educativa “Chavinillo”, Lima – 2020 - Quispe Vargas, Esthefanny Jhasmin (2021)
The purpose of this research was to determine the type of relationship between learning styles and reading comprehension in students of the IV cycle of primary education of the Educational Institution "Chavinillo", Lima - 2020. The study was basic, not experimental. and correlational design. The population consisted of 100 students, from which we obtained a sample of 68 students. A learning styles questionnaire was used as an instrument for the learning styles variable. which measured the visual, auditory and kinesthetic style dimensions and for the reading comprehension variable, a reading comprehension test was used in its three dimensions: literal, inferential and critical. Once the application of the research instruments was completed, the data obtained was processed. Spearman's Rho Nonparametric correlation coefficient was applied for hypothesis testing, which applies to ordinal variables and thus determine the degree of relationship, obtaining a value of 0.000<0.05, which is why it was concluded that there is a _x000D_ high positive relationship between the styles learning and reading comprehension.